THE INFLUENCE OF SOCIAL STUDIES LEARNING, GENDER, AND PARENTING STYLE ON THE SOCIAL SENSITIVITY OF EIGHTH-GRADE STUDENTS AT PUBLIC JUNIOR HIGH SCHOOLS IN CENTRAL SLEMAN REGENCY. - Achmad Faisal Albani; Sunarti (Jurnal Sosialita, 2026)
This study aims to determine the influence of Social Studies Learning, Parenting Style, and Gender on the Social Sensitivity of eighth-grade students at public junior high schools in the central area of Sleman Regency. The research employed a quantitative approach using a survey method. The sample consisted of 358 students (175 male and 183 female), selected through a simple random sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results of the study indicate that: (1) Social Studies Learning has a positive and significant effect on students’ Social Sensitivity and is the most dominant variable, as indicated by a t-value of 11.707, a significance level of 0.000, and the highest Beta coefficient of 0.532. This finding confirms that Social Studies Learning is the most influential factor in enhancing students’ Social Sensitivity; (2) Parenting Style also has a significant effect on Social Sensitivity, with a t-value of 6.201, a significance level of 0.000, and a Beta coefficient of 0.278, indicating that it remains an important supporting factor in the formation of students’ social behavior; (3) Although Gender shows a statistically significant effect (Sig. = 0.030), its Beta coefficient is very small and negative (–0.085), suggesting that it is not a dominant factor in the research model; (4) Simultaneously, the three independent variables have a significant effect on students’ Social Sensitivity, as evidenced by an F-value of 117.284 with a significance level of 0.000. Thus, this study concludes that Social Studies Learning is the most dominant factor influencing students’ Social Sensitivity, supported by the contribution of Parenting Style, while Gender does not serve as a primary factor in the model